Sulfate reduction and alterability of sulfur species in sediments of an estuary with irregular hydrological regime (Ocean and Coastal Research, 2021)
The irregular hydrological regime in Patos Lagoon estuary has been suggested as having a distinctive influence on sulfur speciation in sediments. We performed an investigation for different prolonged hydrological conditions focusing on the distribution of sulfides (acid volatile sulfide (AVS), chromium reducible sulfide (CRS), and Free-S2-) in sediment cores from salt marsh and non-vegetated shallow zone. Significant differences in sulfides content and distribution between the different hydrological periods were found. The predominance of more reducing conditions was observed during the freshwater period. It reflects a higher total reducible inorganic sulfur (TRIS) content in this period, with a great accumulation of AVS in sediments (> 100 mg kg-1). In the maximum salinity period, more oxidizing conditions prevailed, which significantly decreased the concentrations of metastable sulfides. The intense bioirrigation process exerts control over sulfide formation and distribution, which is as important as that exerted by the variations of the hydrological regime.